2011
DOI: 10.5851/kosfa.2011.31.1.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lotus (Nelumbo nucifera) Leaf Powder on the Quality Characteristics of Chicken Patties in Refrigerated Storage

Abstract: This study was aimed at comparing the pH, color, thiobarbituric acid (TBA), volatile basic nitrogen (VBN), textural properties, and sensory evaluations of chicken meat patties containing lotus (Nelumbo nucifera) leaf powder, and assessing their shelf-life at refrigeration temperature (4±1 o C). In the refrigerated storage, the pH, lightness, yellowness, springiness values, and sensory properties scores of the control as well as all the treated samples decreased as the storage increased. The hardness, gumminess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 47 publications
4
20
2
1
Order By: Relevance
“…Simultaneously, the highest amount of WGH decreased springiness and chewiness. Similar trends in springiness and chewiness were observed by Choi et al (2011), when different amounts of lotus leaf powder were added to chicken meat patties. Recent studies have reported that frankfurters manufactured with addition of 25 g/100 g walnut were significantly harder and chewier as well as less springy than frankfurters without any additives (Ayo, Carballo, Solas, & Jim enezColmenero, 2008 that shear force and binding strength of beef steaks prepared with 10 g/100 g or more of walnut were significantly reduced (Jim enez- Colmenero et al, 2003;Serrano et al, 2007;Serrano et al, 2006).…”
Section: Tablesupporting
confidence: 74%
“…Simultaneously, the highest amount of WGH decreased springiness and chewiness. Similar trends in springiness and chewiness were observed by Choi et al (2011), when different amounts of lotus leaf powder were added to chicken meat patties. Recent studies have reported that frankfurters manufactured with addition of 25 g/100 g walnut were significantly harder and chewier as well as less springy than frankfurters without any additives (Ayo, Carballo, Solas, & Jim enezColmenero, 2008 that shear force and binding strength of beef steaks prepared with 10 g/100 g or more of walnut were significantly reduced (Jim enez- Colmenero et al, 2003;Serrano et al, 2007;Serrano et al, 2006).…”
Section: Tablesupporting
confidence: 74%
“…These results indicate that increasing wheat sprout level can decrease the hardness of cookies due to the water holding capacity of wheat sprout. Choi et al (2011) have reported that chicken meat patties added with lotus leaf powder have lower values of hardness compared to control patties. An et al (2010) has reported that the shear forces of meat products are gradually decreased in dietary fiber content.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study has suggested a malondialdehyde concentration of 0.5 mg/kg as a threshold value for the perception of rancidity by consumers (38). Generally, lipid oxidation leading to rancidity is one of the most important changes during food storage and production (32).…”
Section: Changes In Tbars Valuesmentioning
confidence: 99%